(untitled) (Journal of the College of Education for Women, 2019)
Continuous conflict between Parisian and Ottoman states the results that Iraq became asaground for their battles which leads to their own interests in Iraq which are shape theirstrategy. The conflict continues for long time. In spite of, they signed many treatments andprotocols between the two sides, as Arzarom treaty , the first and the second, Tahran protocols, and Astana protocol. This conflict, no sides of them to dose any part of their land, but thesetreaties leaded to a big loss to Iraq ,which lost parts of it’s land and water area in Ahwaz andshatt AL-Arab, so, Iraq became as a smoth target for their interests, and lost itssovereignty,and lost self-govern of the country country . so the research concludes thefollowing.